Do Social Inequalities in Smoking Differ by Immigration Status in Young Adults Living in an Urban Setting? Findings From the Interdisciplinary Study of Inequalities in Smoking - Jodi Kalubi; Zobelle Tchouaga; Adrian Ghenadenik; Jennifer O'Loughlin; Katherine L Frohlich (SAGE Publishing, 2020)
Objectives: We assessed whether social inequalities in smoking observed among young adults born in Canada were also apparent in same-age immigrants. Methods: Data were drawn from an investigation of social inequalities in smoking conducted in an urban setting (Montreal, Canada). The sample included 2077 young adults age 18 to 25 (56.6% female; 18.9% immigrants who had lived in Canada 11.6 (SD 6.4) years on average). The association between education and current smoking was examined in multivariable logistic regression analyses conducted separately in young adults born in Canada and in immigrants. Results: About 19.5% of immigrants were current smokers compared to 23.8% of young adults born in Canada. In immigrants, relative to those with university education, the adjusted odds ratios (OR) (95% confidence interval) for current smoking were 1.2 (0.6, 2.3) among those with pre-university/vocational training and 1.5 (0.7, 2.9) among those with high school education. In non-immigrants, the adjusted ORs were 1.9 (1.4, 2.5) among those with pre-university/vocational training and 4.0 (2.9, 5.5) among those with high school. Conclusion: Young adults who had immigrated to Canada did not manifest the strong social gradient in smoking apparent in young adults born in Canada. Increased understanding of the underpinnings of this difference could inform development of interventions that aim to reduce social inequalities in smoking.